Gender equality through women's empowerment strategies and approaches - Singh, Surendra 1943 Dec. 5.; Srivastava, S. P. 1940- (Bharat Book Centre, 2001)
Contributed articles presented at the International Conference on Gender Equality Through Women's Empowerment: Strategies and Approaches on March 7-9, 1997, Lucknow, India with special focus on Indian situations.